Pemisahan Fungsi Regulator dan Pengelola BUMN Pasca Reformasi Kelembagaan 2025: Desain Akuntabilitas dan Good Governance (SETARA : Jurnal Ilmu Hukum, 2025)
This article examines the legal design for separating regulatory and state-owned enterprise management functions after Indonesia's 2025 institutional reform in the state-owned enterprise sector. The issue is legally important because the reform restructures the role of the state through the creation and adjustment of institutions that handle policy, supervision, investment management, and operational holding functions, while simultaneously raising risks of overlap, weakened accountability, and conflicts of interest. Using normative legal research with statutory, conceptual, and policy approaches, this article analyses Law Number 19 of 2003, Law Number 1 of 2025, Law Number 16 of 2025, Government Regulation Number 10 of 2025, and Government Regulation Number 15 of 2025. The article argues that the 2025 reform has moved toward a clearer institutional distinction between regulator, supervisory authority, and enterprise manager, but the design will only produce good governance if it is accompanied by auditable delegation boundaries, integrated internal control, conflict-of-interest management, and transparent responsibility between BP BUMN, the investment body, and the operational holding structure.
Keywords: State-Owned Enterprises; Institutional Reform; Accountability; Governance; Conflict of Interest